Phototriggered labeling and crosslinking by 2-nitrobenzyl alcohol derivatives with amine selectivity. Issue 15 (27th January 2020) - Wang, Chenxi; Liu, Yuan; Bao, Chunyan; Xue, Yuan; Zhou, Yaowu; Zhang, Dasheng; Lin, Qiuning; Zhu, Linyong
Abstract : 2-Nitrobenzyl alcohol was developed as a new photoreactive group with amine selectivity, which exhibited efficient labeling and crosslinking of biomolecules. Abstract : Here we report the use of 2-nitrobenzyl alcohol (NB) as a photoreactive group with amine selectivity and explore its applications for photoaffinity labeling and crosslinking of biomolecules. This work confirms that NB is an efficient photoreactive group and has great potential in drug discovery, chemical biology and protein engineering.